Retrofitting commercial motorbikes into electric motorbikes - Abdullah, Mohd Rajmin Affendi; Mohamad Hanif, Noor Hazrin Hany; Toha @ Tohara, Siti Fauziah; Kamisan, Nor Azam (USM, 2017)
The existence of Electric Vehicles (EV) such as electric cars, buses and trams, has gained its prominence since these past few decades, primarily contributed by the environmental and economic factors. It is until recently that the automotive market shifted into the production of electric motorbikes. One criteria that stands out about the electric motorbikes as compared to others is the instantaneous power delivered by the motor. However, the implementation of electric motorbike requires that it has to be built from scratch, which in turn, defeats the cost-saving purposes. Therefore, the aim of this research is to retrofit a commercial motorbike into an electric motorbike by replacing the fuel storage and internal combustion engine with batteries and a DC motor. A Honda CBR 250cc motorbike has been used for this study. We scanned the frame of the motorbike using a special 3D scanner machine to obtain its accurate dimensions. The battery and motor housings were then designed based on the acquired dimensions, and static analysis was later conducted to estimate their strengths. The motor and battery housings were then fabricated and tested on the motorbike. It is hoped that the outcome of this research will attract current commercial motorbike users to retrofit their motorbike into an electric bike.